Recognition of Customary Land Rights Based of Krik Slamat - Dianto, Dianto; Absori, Absori; Dimyati, Khudzaifah; Wardiono, Kelik (Faculty of Law, Universitas Pattimura, 2023)
Introduction: The recognition of customary land rights based on local values has undergone several shifts in value, giving rise to state doubts about its existence. Purposes of the Research: Therefore, this research aimed to examine the recognition of customary land rights of the Pusu customary community in Sumbawa based on the value of 'krik slamat'.Methods of the Research: This non-doctrinal research was conducted using a sociological approach to investigate the formation and functioning of the law. This method also discovers the philosophical values embodied in empirical law by objectifying the values that live in society, in this context the objectification of values is carried out with the concept of recognizing norms that live in society.Results of the Research: The results showed that, first, the recognition of land rights of the Pusu community was conducted with 'rpulung' based on the value of 'krik slamat' containing elements of religion, democracy, and justice. Second, in 'krik slamat', which serves as a philosophical foundation in the formation of the law, hence, 'pulung' is born in the form of norms.